Strong convergence of an explicit iteration process for a totally asymptotically II-nonexpansive mapping in Banach spaces - Mukhamedov, Farrukh; Saburov, Mansoor (Elsevier, 2010)
In this work we prove the strong convergence of an explicit iterative process to a common fixed point of a totally asymptotically I-nonexpansive mapping T and a totally asymptotically nonexpansive mapping I, defined on a nonempty closed convex subset of a uniformly convex Banach space.